2010
DOI: 10.1177/1938640010363172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Alkane Vapocoolant Spray on Pain Intensity Prior to Digital Nerve Block for Ingrown Nail Surgery

Abstract: Needle penetration and local anesthetic infiltration are 2 painful steps that cause considerable stress and anxiety during digital nerve block, which is the most frequently used regional anesthesia for ingrown nail surgery. The purpose of this study was to evaluate the effectiveness of topical alkane vapocoolant spray in decreasing pain during digital nerve block for ingrown nail surgery. The authors conducted a prospective, randomized clinical trial with 62 patients who underwent big toenail surgery. Prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…A study by Kose and colleagues reported a similar finding when topical alkaline vapocoolant spray’s effectiveness was evaluated. While the spray was found to relieve pain during initial skin penetration, VAS scores during injection of solution were not significantly decreased [ 21 ]. These studies suggest that the topical agents are not effective in relieving pain that is originated from the infiltration of the anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kose and colleagues reported a similar finding when topical alkaline vapocoolant spray’s effectiveness was evaluated. While the spray was found to relieve pain during initial skin penetration, VAS scores during injection of solution were not significantly decreased [ 21 ]. These studies suggest that the topical agents are not effective in relieving pain that is originated from the infiltration of the anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Extended waiting time can allow a patient to brood on upcoming surgery and may also exacerbate the feeling of anxiety. 1,4,13 Needle penetration and anesthetic infiltration were reported as the 2 painful steps that cause stress and anxiety in patients undergoing nail surgery. 13 Past experience with severely painful nail trauma such as trapping in a door or crushing with a hammer, leading the patient to associate the nail site with extreme pain, may also increase the anxiety and fear of nail surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Franko and Stern 13 prospectively defined a change in 2 points on a Likert pain scale as clinically meaningful, however the average pain reported by participants was approximately 3 in both groups. The pain scores reported by Kose et al 28 during injection were similarly low at 2.43 and 1.32 in the control and intervention groups, respectively. The NPWT dressing changes represented in this study report higher pain scores with and without intervention, providing greater opportunity to appreciate benefit in pain reduction.…”
Section: Discussionmentioning
confidence: 67%